Ali je vzrok upada populacije jerebice Perdix perdix v Sloveniji prikrita kompeticija s fazanom Phasianus colchicus? - Vrezec, Al (Acrocephalus, 2006)
Changes in agriculture are believed to be the main reason for the drastic decline in the Grey Partridge Perdixperdix population in Europe since 1950. Tompkins et al. (1999) suggested that apparent competition with the Pheasant Phasianus colchicus could also be responsible. This is an indirect interactionmediated by parasitic nematode Heterakis gallinarum. The parasite is transmitted from Pheasant to Grey Partridge, seriously affecting the latterspecies and, to a lesser extent, the reservoir host species, the Pheasant. The final effect is therefore competitive exclusion of Grey Partridge from the system. In Slovenia, the population of Pheasant increased, according to hunters' data, 11.5-fold in the 1949 - 1972 period, as a consequence of intensive input of reared birds. The author of the present paper tried to evaluate the critical point / year when the effect of competitive exclusion began to be expressed. This was done, arbitrarily, in two ways: as a temporal unit of growth at half growth (t50) in the logistic growth curve of the Pheasant population, and as the year of population maximumin Grey Partridge. The critical point appeared to be between the years 1958 and 1959. Both Pheasant and Grey Partridge populations showed a positive population trend before that period, but that of the latter then became negative, while the Pheasant trend remained significantly positive. Apparent competition is suggested as the main reason, although other reasons (eg. habitat changes) could not be eliminated, since the degree of influence of parasite infection on the Grey Partridge population is not clear. For effective Grey Partridge conservation and population increase, the author suggests a systematic study of habitat selection, ecological densities and population size of both species in Slovenia. (Abstract truncated at 2000 characters)
Keywords: Birds; Ekosistem; Parasitology; Populacijska dinamika; Ptice; Growth And Development; bird; jerebice; Ecosystem; Slovenia; Slovenija; Population Dynamics